The portrayal of family roles in selected Maranao folk literature - Agbisit, Kiana Aurora L. (College of Home Economics, University of the Philippines Diliman, 2019)
Under an overarching objective of cultural heritage preservation, the study aimed to describe and analyze the portrayal of the clothing and family roles in selected Maranao folk literature. Six stories were selected from The Agamaniyog Folktales published by the University Research Center of the Mindanao State University. The themes and character roles (duties and characteristics) were determined through textual analysis. The character's clothing in the text and illustrations was described using the classification system of dress developed by Roach and Eicher (1992, in Eicher, Evenson, & Luiz, 2015). The clothing and roles were simultaneously interpreted in order to form connotative meanings per family role (e.g. the wife role displaying the most ornamentation, such as jewelry and the pattern of her malong, among the female roles. This reflected the emphasis on beauty and the expectations placed on the wife to follow traditional ideals). The resulting meanings were compared with academic publications about Maranao culture to check for consistency with Maranao family roles. The portrayals were found to be generally consistent in terms of clothing. It was concluded that depictions of clothing were indeed capable of conveying deeper information about the characters wearing them and the cultural context to which both belonged. The function of folk literature as a means of education and as a display of character patterns of social behavior was also highlighted. This implied that the study of clothing depictions in literature as vehicles for cultural heritage preservation shows promise, and that a nationalistic approach to the study of folk literature with the aim of preservation should be done. In the future, this study can serve as a source for further study on Maranao family roles and their clothing. It is recommended to expand the research for a deeper analysis on the variations in clothing observed in the study (e.g. the different ways of tying malong), to further understand the reasoning behind the depictions of clothing and their embedded symbolic meaning.